Peningkatan Kemampuan Bahasa Indonesia Mendeskripsikan Tempat Sesuai Denah melalui Metode Kerja Kelompok Siswa Kelas IV SD Negeri 011 Pulau Kedundung - Lumbarina, Lumbarina (GERAM, 2018)
Indonesian learning outcomes in the material describing the place in accordance with the plan / picture in grade IV SDN 011 Pulau Kedundung, Kuantan Tengah District, Kuansing Regency, is still low, so the learning outcomes have not fulfilled the KKM set by the school, namely 70, Class Action Research is carried out to improve student learning skills by using group work method in odd semester 2016/2017 school year. This study was conducted in two cycles, each cycle consisting of two meetings through four stages, namely planning, implementing, observing and reflecting. Student learning activity data is analyzed by determining the number and percentage of students involved at each meeting. The results showed that learning activities and student learning outcomes experienced improvement where in the initial data of the number of students who took the pre cycle post test (repeat test) as many as 28 people, it turned out that 13 people could be declared complete (46.4%) because the values ​​obtained were the same or exceed the KKM (Minimum Completion Criteria) and the remaining approximately 13 people are declared as having not passed (53.6%). after the actions taken in the first cycle student learning outcomes have increased, it turns out that 18 people can be declared complete (64.3%) because the value obtained has the same or exceeded the KKM (Minimum Completion Criteria) and the remaining about 10 people declared incomplete (35.7 %), and cycle II students turned out to be 25 people declared complete (89.3%) because the value obtained was the same or exceeded the KKM (Minimum Completion Criteria) and the remaining only 3 people were declared incomplete (10.7%). From this data it can be concluded that the use of group work methods can improve the learning outcomes of Indonesian students.